Electrochemical Studies Of Hydrolytic Products From Refined Palm Oil With Immobilized Enzymes At Modified Carbon Electrodes - Jarjes, Zahraa A. (2012)
This work describes the effect of pH, temperature, incubation time, and substrate and enzyme weights on the hydrolysis of refined palm oil using the commercial lipase from the yeast Candida rugosa. It was found that the hydrolysis was optimum at pH 7.5, temperature 37 °C, incubation time 60 min and the enzyme and substrate weights of 0.1 and 2 g, respectively. The released fatty acids were used as a substrate for lipoxygenase immobilized on modified Nafion membrane carbon electrode and the current generated was studied by cyclic voltammetry. Potassium buffer at pH 7 and 0.4 mg of lipoxygenase was found to be crucial in order to produce a higher current density.